2009
DOI: 10.1007/bf03165972
|View full text |Cite
|
Sign up to set email alerts
|

Role of naturally-occurring plant sterols on intestinal cholesterol absorption and plasmatic levels

Abstract: Cardiovascular disease is a major health problem in developed countries although its incidence is relatively lower in Mediterranean countries which is partly ascribed to dietary habits. Epidemiologic evidence shows that elevated serum cholesterol, specifically low-density lipoprotein cholesterol (c-LDL), increases cardiovascular disease. Phytosterols are bioactive compounds, found in all vegetable foods, which inhibit intestinal cholesterol absorption and, therefore, have a serum cholesterol-lowering effect. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 73 publications
0
10
1
Order By: Relevance
“…Regarding the possible contribution of PSO-UM to dietary intake of phytosterols it must be noticed that, as general nutritional suggestion considers a daily intake of 2 g significantly effective against mild hypercholesterolemia, an amount comprised between 5 and 10 g of PSO-UM may contribute for almost half of that quota. The reported dietary intake of phytosterol for european non vegetarian populations, comprised between 160 and 360 mg/day, may be almost triplicated by the daily administration of the above mentioned dosage of PSO-UM [33,34]. The use of specific health claims regarding plant stanol/sterol esters efficacy in the improvement of blood cholesterol profile has been recently awarded by the European Food Safety Authority, making renewable plant sources of these substances even more attractive from the nutraceutical and commercial standpoint [35].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the possible contribution of PSO-UM to dietary intake of phytosterols it must be noticed that, as general nutritional suggestion considers a daily intake of 2 g significantly effective against mild hypercholesterolemia, an amount comprised between 5 and 10 g of PSO-UM may contribute for almost half of that quota. The reported dietary intake of phytosterol for european non vegetarian populations, comprised between 160 and 360 mg/day, may be almost triplicated by the daily administration of the above mentioned dosage of PSO-UM [33,34]. The use of specific health claims regarding plant stanol/sterol esters efficacy in the improvement of blood cholesterol profile has been recently awarded by the European Food Safety Authority, making renewable plant sources of these substances even more attractive from the nutraceutical and commercial standpoint [35].…”
Section: Resultsmentioning
confidence: 99%
“…Of particular interest to the aims of the present study, several previous studies have shown that the lower rates of diabetes often observed in the female populations of human and animal models strongly suggest that the sex steroid hormones 17β-estradiol (E2) manifest interesting anti-diabetic and antioxidant actions [6,7,28,29]. One of the therapeutic approaches proposed for the control of postprandial hyperglycemia is to retard the absorption of glucose and lipid through the inhibition of lipid and carbohydrate-hydrolyzing enzymes, namely disaccharidases and lipases, in the digestive organs [4,10,15,18,19,24].…”
Section: Introductionmentioning
confidence: 99%
“…PS are thought to act primarily in the intestinal lumen, displacing the cholesterol from mixed micelles and, consequently, increasing the amounts excreted by faeces. In addition to that, taking into account that the intestinal cholesterol absorption is a multistep process, PS may also act: a) attenuating the NPC1L1 gene expression, which may result in a lower cholesterol uptake from the lumen; b) lowering the cholesterol esterification rate by the ACAT2 (acylCoA cholesterol acyltransferase) and, consequently, the amount of cholesterol secreted into the circulation from the enterocytes via the chylomicrons and c) upregulating the expression of ABCtransporters ABCG5 and ABCG8 in intestinal cells, which may result in an increased excretion of cholesterol by the enterocyte back into the lumen (22).…”
mentioning
confidence: 99%
“…Traditionally, plant sterols from the habitual diet have not been considered to have any significant effect on the serum cholesterol level but several trials concluded that doses as lower as those obtained from traditional food have an effect on cholesterol absorption (22). Moreover, recent epidemiological (1,11) and clinical (4,21) studies have shown that presence of PS at normal diet levels are also effective lowering total and LDL serum cholesterol since they affect wholebody cholesterol metabolism even at those moderate doses (21).…”
mentioning
confidence: 99%